CHFR Protein Regulates Mitotic Checkpoint by Targeting PARP-1 Protein for Ubiquitination and Degradation - Kashima, Lisa (American Society for Biochemistry and Molecular Biology, 2012)
The mitotic checkpoint gene CHFR (checkpoint with forkhead-associated (FHA) and RING finger domains) is silenced by promoter hypermethylation or mutated in various human cancers, suggesting that CHFR is an important tumor suppressor. Recent studies have reported that CHFR functions as an E3 ubiquitin ligase, resulting in the degradation of target proteins. To better understand how CHFR suppresses cell cycle progression and tumorigenesis, we sought to identify CHFR-interacting proteins using affinity purification combined with mass spectrometry. Here we show poly(ADP-ribose) polymerase 1 (PARP-1) to be a novel CHFR-interacting protein. In CHFR-expressing cells, mitotic stress induced the autoPARylation of PARP-1, resulting in an enhanced interaction between CHFR and PARP-1 and an increase in the polyubiquitination/degradation of PARP-1. The decrease in PARP-1 protein levels promoted cell cycle arrest at prophase, supporting that the cells expressing CHFR were resistant to microtubule inhibitors. In contrast, in CHFR-silenced cells, polyubiquitination was not induced in response to mitotic stress. Thus, PARP-1 protein levels did not decrease, and cells progressed into mitosis under mitotic stress, suggesting that CHFR-silenced cancer cells were sensitized to microtubule inhibitors. Furthermore, we found that cells from Chfr knockout mice and CHFR-silenced primary gastric cancer tissues expressed higher levels of PARP-1 protein, strongly supporting our data that the interaction between CHFR and PARP-1 plays an important role in cell cycle regulation and cancer therapeutic strategies. On the basis of our studies, we demonstrate a significant advantage for use of combinational chemotherapy with PARP inhibitors for cancer cells resistant to microtubule inhibitors.